Interstícios e conexões na paisagem do rio Paranaíba em Itumbiara (1974-2015) - Reis, Mônica Otero de Melo dos (2020)
Since the formation of the town of Itumbiara, located in the interior of Goiás, on the border with Minas Gerais, several processes and dynamics have been established with the inhabitants. This work aims to analyze the differentiated social relations established with the Paranaíba River and its effects on the urban landscape of Itumbiara. The river permeates the urban perimeter of the city, having elements that in its historical trajectory reveal and translate the diversity of phenomenas with direct influence on sociological relations, on the urban layout of the city and on the river itself: the Affonso Penna Pensile Bridge, the river procession in honor of Nossa Senhora das Graças and the Beira Rio Avenue. The time clipping covers from 1974 to 2015, the period when the construction of the Furnas Hydroelectric Power Plant in Itumbiara began, due to the enormous energy potential attributed to the Paranaíba River. The symbolism of the river Procession in homage to Nossa Senhora das Graças will run from the miracle to the established foot and river routes, within the same period of coverage. The processes of project, displacement, reallocation of the Affonso Penna Pensile Bridge will be approached by the imaginary and define the limit of the time cut of the research, one year after its collapse in 2014. The Beira Rio Avenue, integrating the analyzed elements related to the Paranaíba River, comprising from the landscape project, the revitalization project, and the interlacing occurred in this context. The methodological approach is based on the bibliographic review and the survey of documentary and photographic data. The systematization and research of the work was carried out from the analysis and understanding of the texts and works of authors and scholars of the subject. The maps and surveys aimed to translate the data collected.